Design, synthesis and biological evaluation of benzoxazolinone-containing 1, 3, 4-thiadiazoles as TNF-α inhibitors. Issue 4 (April 2019) - Haider, Saqlain; Alam, Mohammad Sarwar; Hamid, Hinna; Dhulap, Abhijeet; Kumar, Deepak
Abstract: A library of nineteen benzoxazolinone-based 1, 3, 4-thiadiazoles has been synthesized and screened for their anti-inflammatory activity. The compound1f exhibited a potent anti-inflammatory activity with an inhibition of 65.83% and 32.50% after 3 h and 5 h respectively. It also exhibited a significant in vitro (p < 0.01), TNF- α inhibitory activity with 51.44 % inhibition. The compound1f showed hydrogen bonding with GLN 61 and interactions with TYR 119, TYR 151 and GLY 121. The histopathology report showed that none of the compounds caused gastric ulceration. The results from the in vivo & in vitro antiinflammatory activity along with In Silico studies exhibit that benzoxazolinone-based 1, 3, 4-thiadiazoles may be used in the future development of anti-inflammatory drugs.